Phases of Forgiveness in Early Adult Women with Parental Infidelity - Manoe, Eunice Christine (Salasika, 2024)
Infidelity in marital relationships is a pervasive phenomenon with a propensity to increase over time. Infidelity often involves children's awareness, leading to adverse impacts on parent-child relationships, children's self-image and identity, mental health, and their future romantic relationships. Although substantial research has been conducted on the forgiveness process among couples, there remains a need for further exploration into the forgiveness process in children, particularly young adults, who have experienced parental infidelity. This study aims to investigate the stages of forgiveness in young adults who have encountered infidelity by both parents. Employing a phenomenological qualitative approach, this research involved in-depth interviews with two young adult women who experienced parental infidelity. The findings indicate that both participants expressed a willingness to forgive both parents involved in the infidelity. However, the forgiveness process varied between parents. Forgiveness towards the mother advanced to the deepening stage (Participant 1) and the action stage (Participant 2), while forgiveness towards the father was impeded, halting at the disclosure stage. The father's lack of demonstrated change in attitude or remorse following the affair, the absence of the father's alignment with family values, the child's perception of the affair, and the father's overall behavior and attitude were identified as barriers to forgiving the father. This study highlights the complexity of the forgiveness process in young adults dealing with parental infidelity and underscores the need for tailored support mechanisms to facilitate forgiveness and emotional healing.